2009
DOI: 10.1111/j.1582-4934.2008.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone signalling complexes in Alzheimer's disease

Abstract: Molecular chaperones and heat shock proteins (Hsp) have emerged as critical regulators of proteins associated with neurodegenerative disease pathologies. The very nature of the chaperone system, which is to maintain protein quality control, means that most nascent proteins come in contact with chaperone proteins. Thus, amyloid precursor protein (APP), members of the gamma-secretase complex (presenilin 1 [PS1] collectively), the microtubule-associated protein tau (MAPT) as well as a number of neuroinflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 133 publications
(146 reference statements)
2
80
0
Order By: Relevance
“…Recent reports showed that low molecular weight drugs including small organic molecules, peptides, small molecular chaperones, enzymes, and antibodies are gaining attention for the treatment of AD (11)(12)(13). The concept of using proteases and peptides as therapeutic agents is common.…”
mentioning
confidence: 99%
“…Recent reports showed that low molecular weight drugs including small organic molecules, peptides, small molecular chaperones, enzymes, and antibodies are gaining attention for the treatment of AD (11)(12)(13). The concept of using proteases and peptides as therapeutic agents is common.…”
mentioning
confidence: 99%
“…Whereby, molecular chaperones make sure that other proteins arrive safely and are functional at their destination within the cell. They also ensure that proteins deemed to be 'ill-behaved' or abnormal are destroyed [249][250][251].…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
“…Hsps with a molecular weight of 60 kDa or more possess an ATPbinding site and are actively involved in the process of refolding misfolded proteins. Small Hsps, with a molecular weight of 40 kDa or less, lack this ATP-binding site and assist the classic Hsps in their refolding function [249][250][251]. Several heat shock proteins can be found in mitochondria, namely the classic Hsps Hsp60, mtHsp70 (mortallin), mtHsp90 (TRAP-1) and Hsp78 and small Hsps Hsp10, Hsp27, αB-crystallin, Hsp22, mtHsp40 [251][252][253][254][255].…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently is also suggested the participation of another isomerases like cyclophilin family, but is under research (Koren et al, 2011). In this matter chaperones, specially Hsp90, also can be necessary to maintain Tau in a non-aggregated state, a consequence that may ultimately be deleterious for the brain under pathological conditions (Koren et al, 2009). …”
Section: Impact Of Tau Conformational Change During Aggregation Processmentioning
confidence: 99%